Differences in sexual size dimorphism among farmed tilapia species and strains undergoing genetic improvement for body weight - Lind, C.E.; Safari, A.; Agyakwah, Seth K.; Attipoe, F.Y.K.; El-Naggar, G.O.; Hamzah, A.; Hulata, G.; Ibrahim, N.A.; Khaw, H.L.; Nguyen, N.H.; Maluwa, A.O.; Zaid, M.; et al. (Elsevier, 2015)
Many tilapia (Oreochromis spp.) farmers produce all-male populations because of the superior growth rate of males compared to females. To investigate differences in body weight at harvest of males and females among different tilapia strains, we analyzed data from 62,787 individuals collected from pedigreed breeding programs of O. niloticus (GIFT from Malaysia, the Abbassa line from Egypt, and the Akosombo line from Ghana), O. shiranus (the Bunda College-Domasi selection line), O. aureus (a selection line under development in Abbassa, Egypt, and a selection line from Israel) and a synthetic selection line of Red tilapia under development in Jitra, Malaysia, derived from stock from Malaysia, Taiwan and Thailand (O. sp.). Mixed models were separately fitted to the data from each selection line. There was a significant sex effect in all strains (P < 0.001). A significant (P < 0.001) sex by generation interaction was observed in all strains (scale effect, not reversal of rankings), except Red tilapia and O. shiranus. Least squares means showed a large range in the magnitude of body weight differences between sexes across the seven strains. The largest percentage difference between females and males was in O. aureus from Egypt (female body weight was 52.2% that of males at harvest), whereas the smallest difference was observed in the GIFT strain of O. niloticus (female body weight 84.7% that of males). Female to male body weight percentages for Red tilapia, O. shiranus, Egypt O. niloticus, Israeli O. aureus and Ghana O. niloticus were 81.3, 81.0, 69.1, 61.7 and 61.0, respectively. We discuss the results in relation to the potential productivity improvements due to superior growth rates of all-male culture compared to mixed-sex culture in tilapia populations differing in the female to male body weight ratio.